2020
DOI: 10.3390/agronomy10101551
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Uptake in Native Cacao Trees in Agricultural Lands of Bagua, Peru

Abstract: Cadmium (Cd) contamination threatens cocoa farming in the province of Bagua in Amazonas, Peru. This study reports our assessment of Cd concentrations in cocoa farm soils, and in cocoa roots, leaves, testa, and cotyledon, thus evaluating the magnitude of the problem caused by Cd exposure. For our analysis, we sampled agricultural soil, cocoa roots, leaves and pods at 29 farms in the province of Bagua. Concentrations of Cd in each of the samples were measured and correlated with selected variables at each sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
0
20
1
7
Order By: Relevance
“…On the contrary, the Amazon region of Peru is recognized for producing a diverse range of cocoa beans with distinctive sensory attributes (flavor and aroma) that are very different from those of other cocoa production centers, which is why this region was granted the designation of origin "Cacao Amazonas Peru." [10,11] However, although cocoa, as well as coffee, cultivation is the most representative product of the Amazon region and can be very promising for increasing the sustainable development of cocoa activity, phenotypic characteristics of cocoa have not yet been recorded in terms of key descriptors of fruits, seeds, productivity, and sensory properties. In this sense, this research aims to perform the phenotypic characterization of 146 ecotypes of fine-aroma native cocoa from the northeastern zone of Peru.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the Amazon region of Peru is recognized for producing a diverse range of cocoa beans with distinctive sensory attributes (flavor and aroma) that are very different from those of other cocoa production centers, which is why this region was granted the designation of origin "Cacao Amazonas Peru." [10,11] However, although cocoa, as well as coffee, cultivation is the most representative product of the Amazon region and can be very promising for increasing the sustainable development of cocoa activity, phenotypic characteristics of cocoa have not yet been recorded in terms of key descriptors of fruits, seeds, productivity, and sensory properties. In this sense, this research aims to perform the phenotypic characterization of 146 ecotypes of fine-aroma native cocoa from the northeastern zone of Peru.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have reported that the foliar concentration of Cd is comparable with the concentration in beans. 25,31,32 Therefore, the present study was carried out in a greenhouse under controlled conditions. Here, three soils from cacao areas and an andisol were used.…”
Section: Methodsmentioning
confidence: 99%
“…19,24 The absorption of Cd by plants also depends on the soil's physical and chemical characteristics; for example, pH, cation exchange capacity, organic matter and calcium (Ca) concentration have been reported as important variables in the process of Cd absorption. 5,18,22,25 Even farm management practices can affect Cd uptake. 26,27 Available Cd is usually a good predictor of Cd absorbed by cacao plants.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the soil has a low cadmium content, referring to both Peru (Figure 1), and the reports available for South American (Table 1), but research warns that cacao beans can capture cadmium and reach concentrations that are higher than the soil itself (Chávez et al, 2015;Díaz et al, 2018;Engbersen et al, 2019;Oliva et al, 2020). Moreover, most agree that bioaccumulation is higher in roots, leaves, pods and beans, with or without shell (Ramtahal et al, 2019;Barraza et al, 2017;Gramlich et al, 2017;Oliva et al, 2020), which is an aspect that can be analyzed.…”
Section: Cadmium In Cacao Beansmentioning
confidence: 99%
“…Soil generally has a low cadmium content (Kabata-Pendias, 2010), but regardless of the level and origin, the dynamics of the metal depend on its chemical form and the characteristics of the soil (Bravo et al, 2014;Díaz et al, 2018;Scaccabarozzi et al, 2020). This limits or contributes to the mobilization and uptake of cadmium from cacao plants (Gramlich et al 2017;Zug et al 2019); in some plant structures it is accumulative (Hernández-Baranda et al, 2017;Tantalean and Huauya, 2017;Casteblanco, 2018), and reaches concentrations that are higher than in the soil itself (Chávez et al, 2015;Díaz et al, 2018;Oliva et al, 2020). Due to this, the EU and some other countries have implemented standards to classify agricultural soil.…”
mentioning
confidence: 99%